The Role of Arbuscular Mycorrhizal Fungi in Enhancing Productivity, Nutritional Quality, and Drought Tolerance Mechanism of Stylosanthes seabrana - P D.M.H Karti; D A Astuti; S Nofyangtri (Faculty of Animal Science, Bogor Agricultural University, 2012)
Arbuscular Mycorrhizal Fungi (AMF) is a symbiotic association between plant roots and fungi. Their major role is to enhance nutrient and water uptake by the host plants. The objective of this research was to study the role of AMF in enhancing productivity, nutritional quality and tolerance mechanism of Stylosanthes seabrana in drought conditions. This research used a completely randomized design with four treatments: A0 (without AMF), A1 (without AMF in drought), A2 (with AMF), and A3 (with AMF in drought) in S. seabrana. Parameters observed were the soil moisture content, water potential of shoot, relative water content of leaf (RWC), root length, shoot and root dry weight, proline, soluble sugars, crude protein, gas production, and digestibility of organic matter. The data were analyzed with analysis of variance (ANOVA) and the differences between treatments were analyzed with Duncan Multiple Range test. Results showed that inoculation of AMF could enhance leaf water potential, shoot and root dry weight, crude protein, gas production, digestibility of organic matter, but decreased proline and soluble sugars significantly (PS. seabrana seems likely through accumulating organicosmolytes such as prolines and soluble sugars.